2017
DOI: 10.1063/1.4974915
|View full text |Cite
|
Sign up to set email alerts
|

Large rotating magnetocaloric effect in ErAlO3 single crystal

Abstract: Large rotating magnetocaloric effect in ErAlO 3 single crystalMagnetic and magnetocaloric properties of ErAlO 3 single crystal were investigated. Magnetization of ErAlO 3 shows obvious anisotropy when magnetic field is applied along the a, b and c axes, which leads to large anisotropic magnetic entropy change. In particular, large rotating field entropy change from the b to c axis within the bc plane is obtained and reaches 9.7 J/kg K at 14 K in a field of 5 T. This suggests the possibility of using ErAlO 3 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The isothermal The maximum value for −∆S M reaches as high as 41.24 J kg −1 K −1 at around 3.8 K for ∆H = 9 T. This is exceptionally large in comparison with similar rare-earth perovskites, such as RMnO 3 [20][21][22], RFeO 3 [23,24] and other RCrO 3 where R is Ho and Dy [9,10]. Generally, the above mentioned compounds containing magnetic 3d-elements (Mn, Cr and Fe) exhibit less −∆S M in comparison to RAlO 3 [20,25,26], where R is the only magnetic sublattice, due to the presence of negative 3d-4f exchange interactions. In contrast, GdCrO 3 shows larger −∆S M compared to RAlO 3 , indicating that change in magnetic entropy is not simply induced by the ordering of the R-sublattice or the interactions between R-4f and Mn-3d, moreover some new mechanism is responsible for this giant magnetic entropy change.…”
Section: Resultsmentioning
confidence: 91%
“…The isothermal The maximum value for −∆S M reaches as high as 41.24 J kg −1 K −1 at around 3.8 K for ∆H = 9 T. This is exceptionally large in comparison with similar rare-earth perovskites, such as RMnO 3 [20][21][22], RFeO 3 [23,24] and other RCrO 3 where R is Ho and Dy [9,10]. Generally, the above mentioned compounds containing magnetic 3d-elements (Mn, Cr and Fe) exhibit less −∆S M in comparison to RAlO 3 [20,25,26], where R is the only magnetic sublattice, due to the presence of negative 3d-4f exchange interactions. In contrast, GdCrO 3 shows larger −∆S M compared to RAlO 3 , indicating that change in magnetic entropy is not simply induced by the ordering of the R-sublattice or the interactions between R-4f and Mn-3d, moreover some new mechanism is responsible for this giant magnetic entropy change.…”
Section: Resultsmentioning
confidence: 91%
“…[10][11][12][13] In addition, it is important to explore magnetocaloric materials at the cryogenic temperature, which would be beneficial for hydrogen or helium liquefaction and space science. [5,14] Over the past few decades, attention has mostly been paid to cryogenic magnetocaloric materials with rare-earth based alloys and oxides, such as Gd 3 B 5 O 12 (B = Ga, Fe, Al), [15] RM 2 (R = rare earth elements, M = Al, Ni, Co), [16][17][18] RM (M = Zn, Ga), [19][20][21][22] RMX (M = Fe, Co, X = Al, Mg, C), [23,24] R 2 T 2 X (T = Cu, Ni, Co, X = In, Al, Ga, Sn, and so on), [25] R 60 Co 20 Ni 20 (R = Ho and Er), [26] La 1−x Pr x Fe 12 B 6 , [27] Gd 20 Ho 20 Tm 20 Cu 20 Ni 20 , [28] DyNiGa, [2] dual-phase HoNi/HoNi 2 composite, [29] RNO 3 (N = Al, Fe, Mn, Cr, and so on), [30][31][32][33][34][35][36][37] and R 2 M 2 O 7 . [38][39][40][41][42] In particular, recent studies have demonstrated that the Gd 3+ and Eu 2+ ion-based compounds display great MCE performances due to the large angular momentum of the half-filled 4f shell (4f 7 ) and negligible crystal electrical field (CEF) effect with J = S = 7/2, L = 0, with the representative compounds such as GdFeO 3 , [43] GdScO 3 , [44] GdCrO 3 , [45] GdAlO 3 ,…”
Section: Introductionmentioning
confidence: 99%